Protonated nanostructured aluminosilicate (NSAS) reduces plasma cholesterol concentrations and atherosclerotic lesions in Apolipoprotein E deficient mice fed a high cholesterol and high fat diet - Sivak, Olena (BioMed Central, 2009)
The aim of this work was to assess the effect of chronic administration of protonated nanostructured aluminosilicate (NSAS) on the plasma cholesterol levels and development of atherosclerotic lesions in Apolipoprotein (ApoE) deficient mice fed a high cholesterol and high fat diet. Apolipoprotein E (ApoE) deficient mice were divided into the following treatment groups: protonated NSAS 1.4% (w/w), untreated control and 2% (w/w) stigmastanol mixed with high-cholesterol/high-fat diet. Animals were treated for 12 weeks, blood samples were withdrawn every 4 weeks for determination of plasma cholesterol and triglyceride levels. At the end of the study the aortic roots were harvested for assessment of atherosclerotic lesions. NSAS at 1.4% (w/w) and stigmastanol at 2% (w/w) treatment groups showed significant decreases in plasma cholesterol concentrations at all time points relative to the control animals. The lesion sum area in 1.4% (w/w) NSAS and 2% (w/w) stigmastanol groups were significantly less from the control animals. In conclusion, in this study, the effectiveness of chronic administration of protonated NSAS material in the reduction of plasma cholesterol levels and decrease in development of atherosclerotic lesions was demonstrated in Apo-E deficient mice model.